Genetic Variants of Thymic Stromal Lymphopoietin in Nonsteroidal Anti-Inflammatory Drug-Induced Urticaria/Angioedema - Plaza-Serón, María Del Carmen; Blanca-López, Natalia; Pérez-Sánchez, Natalia; Doña, Inmaculada; Acosta-Herrera, Marialbert; Pino-Yanes, María; Flores, Carlos; Cornejo-García, José Antonio; Perkins, James R; Molina, Ana; Torres, Maria José; Blanca, Miguel; et al. (International archives of allergy and immunology, 2016)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most frequent agents involved in hypersensitivity drug reactions, with NSAID-induced urticaria and/or angioedema (NIUA) being the most common entity. Mast cells are key players in NIUA and are activated by thymic stromal lymphopoietin (TSLP). This cytokine functions through recognition by its receptor, composed of IL7Rα (interleukin-7 receptor alpha) and TSLPR (TSLP receptor). These genes have been previously associated with other inflammatory diseases. We assessed the genetic association between single nucleotide polymorphisms (SNPs) in TSLP, IL7R and TSLPR and NIUA in Spanish individuals, using genotyped and imputed data. A total of 369 unrelated NIUA patients and 580 NSAID-tolerant control subjects were included, and 6 SNPs in TSLP, 6 in IL7R and 3 in TSLPR were genotyped. Further variants were imputed using Mach and the 1,000 Genomes Project (Phase 3) data. Association testing and statistical analyses were performed with Mach2dat and R. A total of 139 SNPs were tested for association following quality control. Two SNPs in TSLP (rs1816678 and rs764917) showed a nominal association (p = 0.033 and 0.024, respectively) with NIUA, although these results were not statistically significant after correcting for multiple comparisons. Although TSLP, IL7R and TSLPR are important genes involved in the development of the inflammatory response, we found no significant genetic association with NIUA in our population for common SNPs in these genes.